Identification and analysis of differentially expressed microRNAs in rainbow trout (Oncorhynchus mykiss) responding to infectious hematopoietic necrosis virus infection. (November 2018) - Cao, Yongsheng; Wang, Di; Li, Shaowu; Xu, Liming; Zhao, Jingzhuang; Liu, Hongbai; Lu, Tongyan; Zhang, Qiya
Abstract: MicroRNAs (miRNAs) are a class of regulators essential for numerous biological processes. Infectious hematopoietic necrosis virus (IHNV) is one of the most important viral pathogens in salmon and trout. In this study, the miRNA expression profiles of rainbow trout upon IHNV infection were explored. In total, 392 known miRNAs and 936 novel miRNAs were identified. Twelve known and 13 novel miRNAs were differentially expressed between infected and uninfected fish. Gene Ontology and Kyoto Encyclopedia of Genes and Genomes analyses revealed that certain miRNA target genes were associated with biological regulation, the immune system, and signal transduction. In addition, over- and suppressed expression of miR-146a-3p, miR-155–5p, miR-216a-5p, and miR-499b-5p could respectively increase and decrease viral gene expression in cells and viral titers. MiR-146a-3p and miR-216a-5p inhibited the expression of type-I IFN and the Mx1 gene induced by IHNV. These results provide preliminary insights into the IHNV–host interactions mediated by miRNAs. Highlights: MiRNA responses to IHNV infection were identified in rainbow trout by sequencing. 12 known and 13 novel miRNAs were differentially expressed during IHNV infection. Several differentially expressed miRNAs were predicted to be involved in immunity. MiR-146a-3p, 155–5p, 216a-5p and 499b-5p were positive for IHNV replication. MiR-146a-3p and 216a-5p inhibited IHNV induced type I IFN and Mx1 expression.